2009
DOI: 10.1097/wnr.0b013e3283319e25
|View full text |Cite
|
Sign up to set email alerts
|

Preferential processing of tactile events under conditions of divided attention

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…This conclusion is based on subtraction of the lag caused by the technical implementation from the mean RT of T condition and supported by earlier findings showing about 30-40 ms shorter RTs to tactile than visual stimuli (e.g., [3,5,21]). Following this, tactile instructions would seem to have the potential to enable even faster knee lift reactions than conventionally used visual instruction provided that the onset of the tactile stimulus could be reliably situated to the initial phase of the instructor's leg movement.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This conclusion is based on subtraction of the lag caused by the technical implementation from the mean RT of T condition and supported by earlier findings showing about 30-40 ms shorter RTs to tactile than visual stimuli (e.g., [3,5,21]). Following this, tactile instructions would seem to have the potential to enable even faster knee lift reactions than conventionally used visual instruction provided that the onset of the tactile stimulus could be reliably situated to the initial phase of the instructor's leg movement.…”
Section: Discussionsupporting
confidence: 63%
“…As compared to auditory RTs, tactile RTs have been found to be less affected by distractions such as a concurrent secondary task (e.g., [4]). This is probably because, in contrast to visual and auditory events, tactile events are in direct physical contact with the organism and thus evoke more readily the interest of an organism [5]. Mechanisms to react to tactile stimulation are among the first ones to develop as evidenced by the palmar grasp reflex 2 Advances in Human-Computer Interaction of fetuses [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, attention to tactile stimuli under the involuntary and voluntary movement conditions may become intense compared with the no movement condition. In this respect, Hanson et al [21] demonstrated that temporal tactile perception was fixed despite attentional load. Hence, it seems difficult to attribute our results to the effect of attention.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In our study, although we asked participants to pay attention to tactile stimulus to eliminate the effect of attention, it was seemed that the attention on tactile stimuli in Voluntary and Involuntary conditions might become strong compared to No-movement condition. However, Hanson et al, [16] demonstrated that temporal tactile perception was fixed despite any attentional load. Therefore it is difficult to account for the present results by the effect of attention.…”
Section: Discljssionmentioning
confidence: 97%